Association of Postoperative Antibiotics With Surgical Site Infection in Mohs Micrographic Surgery. Issue 1 (January 2019) - Levin, Ethan C.; Chow, Conroy; Makhzoumi, Zaineb; Jin, Chengshi; Shiboski, Stephen C.; Arron, Sarah T.
Abstract : BACKGROUND: Surgical site infection (SSI) is the most frequent complication of Mohs micrographic surgery. Previous studies have identified risk factors for SSI, but it is not known whether antibiotic prophylaxis mitigates this risk. OBJECTIVE: To measure the association between antibiotic prophylaxis and SSI in a convenience sample of Mohs cases and to report on the utility of propensity scoring to control for confounding by indication in registry data. METHODS: Data were drawn from a pilot quality improvement registry of 816 Mohs cases. The relationship between antibiotic prophylaxis and SSI was assessed with logistic regression modeling using propensity score methods to adjust for confounding. RESULTS: One hundred fifty-one cases were prescribed antibiotic prophylaxis (18.5%). Of 467 cases with follow-up, 16 (3.4%) developed SSI. Infection rates were higher in subjects prescribed prophylaxis, but propensity adjustment reduced this effect. Adjusted odds of infection were 1.47-fold higher in subjects prescribed antibiotics and not statistically significant (95% confidence interval 0.29–7.39; p = .64). CONCLUSION: Although there was no significant difference in SSI among patients prescribed prophylactic antibiotics, statistical precision was limited by the low incidence of infection. Larger population-based prospective registry studies including propensity adjustment are needed to confirm the benefit of prophylactic antibiotics in high-risk surgical cases.